مفهوم جودة المراجعة في ظل الدراسات الأكاديمية و الهيئات المهنية للمراجعة - رحماني, موسى; سردوك, فاتح (Sciences humaines; Vol. 35 (2014): SCIENCES HUMAINES)
الملخص :  يحظى موضوع جودة المراجعة باهتمام كبير من قبل الباحثين في مجال المراجعة، ويرجع السبب في ذلك إلى أن جودة المراجعة العالية تعد السند الأساسي لثقة المستثمرين في المعلومات المالية وغير المالية، كما أنها تلعب دوراً فعالا للمساهمة في النمو الاقتصادي للمجتمع واستقراره المالي، وفي هذا المجال فقد حاولت العديد من الدراسات كشف العلاقة بين جودة المراجعة وجملة من العوامل التي تؤثر فيها، كما أن الاختلاف       في وجهات النظر بين جميع الأطراف المهتمة بعملية المراجعة حول مفهوم جودة المراجعة يشير إلى عدم تبلور هذا المفهوم بشكل نهائي كمفهوم شامل ومرجعي، وهذا ما يتطلب منا الوقوف على دراسة مفهوم جودة المراجعة، وأهميتها وكذلك أهم العوامل المؤثرة فيها.           Abstract:          The subject of quality audit have a great interest by researchers in the audit, due to that the high quality of audit is the backbone of investors confidence in financial and non-financial informations, as they play an active role to contribute to the economic growth of the community and its financial stability, and in this area has tried many studies revealed to the relationship between the quality of auditing and a number of factors that affect them, and the Differences in views among all interested parties on the concept of the audit quality review refers to the non-crystallized of this concept as an overarching concept and final reference, and this requires us to confront the study of the concept of audit quality, and relevance as well as the most important factors affecting it.